قراءة النص المقدس بين التراث الإسلامي ونظريات العلم الحديث (الخطأ بين مقولات تعدد الحق، ومقولات وحدة الحق وخطأ الآخرين) Reading the Holy Text between the Islamic heritage and the theories of modern science: the error between the statements of the plurality of truth, the statements of the unity of truth and the error of others) - Al-Mashrafe, Ibrahim Bin Said Bin Ali; Ali, Asem Shehadeh Saleh (Sakarya University Turkey, 2021)
يسلط هذا البحث الضوء على مفهوم الاجتهاد عند الأصوليين، وأنواع الاجتهاد، والمقولات حول خطأ المجتهد في الفروع والأصول، كما يركز البحث على بعض المدارس النقدية الحديثة في قراءة النص، وموقف المفكرين منها قبولاً أو رفضاً، في حدود موضوعية وهي: علم الأصول، ونظريات ما بعد البنيوية في علم النقد الحديث. من خلال المنهج الوصفي التحليلي. وكان من نتائج هذا البحث: أن نصوص القرآن الكريم ونصوص السنة المطهرة، تحملان وجوهاً لا وجهاً واحداً في المعنى بل لهما عدة تأويلات، والمجتهد المخطئ معذور وله أجر على اجتهاده مادام أنه استفرغ كل ما في وسعه للتوصل إلى الحكم لذا يلزمنا صون ما للمسلم علينا من حقوق، وعدم إصدار أي تهمة إليه ما دام له شبهة دليل شرعي أو عقلي أو لغوي تدرأ عنه الأسماء السلبية والأحكام القاسية. الكلمات المفتاحية: المجتهد، نص مقدس، نقد، البنيوية، مفكر Abstract This research sheds light on the concept of ijtihad among the fundamentalists, the types of ijtihad, and the statements about the error of the mujtahid in the branches and origins. Post-structuralism in modern criticism. Through the descriptive analytical method. One of the results of this research: that the texts of the Noble Qur’an and the texts of the pure Sunnah have two faces, not one face in meaning, but they have several interpretations, and the erring diligent is excused and he is rewarded for his diligence as long as he exhausted everything in his power to reach the ruling. Rights, and not to issue any accusation against him as long as he has a suspicion of legal, mental or linguistic evidence that shields him from negative names and harsh judgments. Keywords: Mujtahid, sacred text, criticism, structuralism, thinker.